Kombinasi pijat skapula dan servikal terhadap nyeri bahu-leher akibat Hemodialisis: Laporan Kasus Klinis - Inayati, Aini; Nuraini, Secaria Putri; Nuraini, Aditya Putri (Borobudur Nursing Review, 2025)
Abstract Patients with Chronic Kidney Disease (CKD) frequently experience musculoskeletal discomfort, including shoulder and neck pain, due to uremic neuropathy, reduced mobility, and prolonged static posture during hemodialysis. Non-pharmacological interventions such as scapula massage and cervical massage may help reduce muscle tension and improve range of motion. The objective of this study is to report the effects of combined scapula massage and cervical massage on shoulder–neck pain in a CKD patient. The method of this study adheres to the CARE (Case Report) Guidelines. The results showed that the patient's pain score decreased from NRS 6 to NRS 2 after three intervention sessions. In conclusion, scapula and cervical massage may serve as safe and effective complementary therapies for reducing musculoskeletal pain in patients with CKD. Keywords: Sapula; Cervical; massage; CKD; Shoulder–neck pain.